The influence of temperature on the deformation behavior, strength and fracture mechanism of the heat-resistant Nickel-based alloy EI698-VD (Fracture and Structural Integrity, 2026)
A detailed investigation was conducted into the fracture mechanisms of cylindrical specimens made of a polycrystalline heat-resistant nickel-based alloy XH73MBTU-VD (EI698-VD), under uniaxial tension in the temperature range of 25–700°C. The presence of both surface and internal defects was identified and subsequently described. The alloy microstructure was observed using scanning electron microscopy and energy-dispersive X-ray spectroscopy methods. In the temperature range of 650 to 700°C, it has been observed that the onset of crack formation occurs at surface defects.  Conversely, at lower temperatures, failure was attributed to the process of ductile growth and the coalescence of pores, leading to the formation of an internal crack. At a test temperature of 400°C and above, the Porteven-Le Chatelier effect (serrated flow) was identified. At temperatures of 25, 400 and 550°C, fracture was accompanied by deformation in different slip planes. An increase in the test temperature was found to result in a change in the slope angle of the slip planes. It was observed that at higher temperatures, there was a significant decrease in plasticity. An excess of 90 times the nominal mass composition of Pb content was detected. A possible cause and mechanism of the steep loss of alloy plasticity with increasing temperature is explained.
Keywords: Nickel-based alloy XH73MBTU-VD (EI698-VD); plasticity; strength; crack; dislocation slip bands; failure analysis